Divergent synthesis of N-heterocycles via controllable cyclization of azido-diynes catalyzed by copper and gold - Shen, Wen-Bo; Sun, Qing; Li, Long; Liu, Xin; Zhou, Bo; Yan, Juan-Zhu; Lu, Xin; Ye, Long-Wu (Nature communications, 2017)
Gold-catalyzed intermolecular alkyne oxidation by an N–O bond oxidant has proven to be a powerful method in organic synthesis during the past decade, because this approach would enable readily available alkynes as precursors in generating α-oxo gold carbenes. Among those, gold-catalyzed oxidative cyclization of dialkynes has received particular attention as this chemistry offers great potential to build structurally complex cyclic molecules. However, these alkyne oxidations have been mostly limited to noble metal catalysts, and, to our knowledge, non-noble metal-catalyzed reactions such as diyne oxidations have not been reported. Herein, we disclose a copper-catalyzed oxidative diyne cyclization, allowing the facile synthesis of a wide range of valuable pyrrolo[3,4- c ]quinolin-1-ones. Interestingly, by employing the same starting materials, the gold-catalyzed cascade cyclization leads to the divergent formation of synthetically useful pyrrolo[2,3- b ]indoles. Furthermore, the proposed mechanistic rationale for these cascade reactions is strongly supported by both control experiments and theoretical calculations. Fused N -heterocycles are structural motifs observed in natural products and bioactive compounds. Here, the authors developed divergent copper- and gold-catalyzed oxidative cyclizations of diynes to two types of tricyclic N -heterocycles and rationalized the product selectivity by theoretical calculations.